In situ formation of Ni3S2–Cu1.8S nanosheets to promote hybrid supercapacitor performance. Issue 18 (12th April 2019) - Liu, Yadong; Liu, Guoqiang; Nie, Xiong; Pan, Anqiang; Liang, Shuquan; Zhu, Ting
Abstract : Ni3 S2 –Cu1.8 S nanosheets were fabricated by a one-step co-sulfurization with in situ ion exchange, demonstrating potential applications in hybrid supercapacitors. Abstract : Homogeneous copper incorporated nickel sulfide (NS) nanosheets were realized via an in situ ion exchange method and one-pot hydrothermal process. Nickel foam (NF) and copper foam (CF) were used as metal sources for the co-formation of Cu1.8 S–Ni3 S2 in the presence of thiourea. As a result of the Cu incorporation, the NF-supported Ni3 S2 nanosheets exhibited improved electronic conductivity with higher electrochemical surface area (ECSA). When evaluated as electrode materials for supercapacitors, the as-obtained active materials demonstrated high specific capacitance (1686 F g −1 at 1 A g −1 ) with excellent cycling performance (95.39% capacitive retention after 10 000 cycles), which may be attributed to the unique structural features as well as the synergistic effect of localized copper species with Ni3 S2 nanosheets.